Natural Killer Cells Eradicate Galectin-1 Deficient Glioma in the Absence of Adaptive Immunity - Baker, Gregory J. (2014)
Natural killer (NK) cells safeguard against early tumor formation by destroying transformed target cells in a process referred to as NK immune surveillance. However, the immune escape mechanisms used by malignant brain tumors to subvert this innate type of immune surveillance remain unclear. Here we show that malignant glioma cells suppress NK immune surveillance by overexpressing the β-galactoside-binding lectin galectin-1. Conversely, galectin-1 deficient glioma cells could be eradicated by host NK cells prior to the initiation of an anti-tumor T-cell response. In vitro experiments demonstrated that galectin-1 deficient GL26-Cit glioma cells are ~3-fold more sensitive to NK-mediated tumor lysis that galectin-1 expressing cells. Our findings suggest that galectin-1 suppression in human glioma could improve patient survival by restoring NK immune surveillance that can eradicate glioma cells.